MRNA formation and function - Richter, Joel D. (Academic Press, 1997)
MRNA Formation and Function presents a compendium of techniques geared exclusively toward the understanding of RNA metabolism. It will be particularly useful because a number of different organisms and systems are employed. Key Features * Isolation and characterization of specific RNA binding proteins * RNA metabolism and associated regulatory proteins * RNA detection and localization * A genetic approach to RNA function.